Marker assisted selection for reproductive mode in BR19 Interspecific Brachiaria Progeny Test with p779/p780 marker: Genotyping the BR19 progeny test for reproduction mode and finding potential facultative apomictic genotypes - Perea, Claudia Samantha; Hernández, Luis Miguel; Jauregui, Rosa (CGIAR Initiative on Accelerated Breeding, 2023)
This report presents the results of genotyping for marker assisted selection on reproductive mode of 601 samples from the BR19 progeny test of the Interspecific Brachiaria breeding program at CIAT. We used the marker p779/p780 for selecting the apomictic hybrids, discarding the sexual plants. For the 3.3% potential sexual plants we detected by this method, we also assessed reproductive mode from the parental plant from which the seeds were collected, to test if it was a case of potential facultative apomixis. We found only one (0.16%) confirmed facultative apomictic genotype- an apomictic genotype from which half of the progeny from the collected seeds were detected to be sexual. This genotype will be kept to further study of facultative apomixis in Brachiaria.